Analysis of the Islamic Banking Performance Using Sharia Conformity and Net Profitability Index Model - Faris Daffa’ Rosyiid; Ahmad Suminto; Naahilah Hunafaa' Al-Qudsy (Journal of Economics, Law, and Humanities, 2025)
Sharia Commercial Bank is a financial institution based on Islamic principles. Mainly, measuring banking performance uses financial ratios, including financial performance in Sharia banking. For this reason, an analysis is needed to measure the level of Sharia compliance without ignoring profitability gains. The Sharia Conformity and Profitability (SCnP) model is an analytical method used to measure the performance of Islamic Banks, and it is suitable and relevant. Sharia conformity aims to evaluate the extent of Sharia banking activities. The quantitative research uses secondary data to examine eight Islamic commercial banks listed by OJK in Indonesia from 2019 to 2023. The collection technique uses documentation from the annual report of Sharia commercial bank, a statistical report obtained from the bank's official website. The data analysis technique uses the SCnP model, which Kuppusamy initiated. Sharia conformity is measured using Sharia Investment, Income, and Profit Sharing Ratio. Meanwhile, measuring profitability uses ROA, ROE, and NPM indicators. The research results show that Sharia Commercial Banks' performance is measured using the SCnP model and divided into four quadrants. The results obtained show that Bank BCAS and BNTBS occupy the Upper Right Quadrant position; Bank BSI, BJBS, and BRKS occupy the upper left quadrant position; BPDS Bank occupies the Lower Right Quadrant position; and Bank BMI and BSB occupy the Lower Left Quadrant position. Future researchers are advised to develop research on assessing the financial performance of Islamic banks using the latest research methods, such as measuring the Banking Islamicity Index, the Maqashid Syariah Index, and the real sector financial performance Index.